New combinations in Potentilla (Rosaceae) for the Nordic Flora - Christenhusz, Maarten J. M.; Väre, Henry (Phytotaxa, 2012)
For an updated checklist of the Nordic Flora, several new combinations are needed in the genera Potentilla (Rosaceae). Combinations for species occurring or cultivated in the Nordic Countries (Denmark, Finland, Iceland, Norway and Sweden) are provided here. The genera are still in need of a worldwide taxonomic revision, where numerous other species of especially Alchemilla and Lachemilla need to be transferred to Potentilla, but this is not within the framework of our study. We restrict us here to species relevant to the Nordic Flora and species cultivated in that area.